Metabolic Changes in Chronic Hepatitis C Patients Who Carry IFNL4-ΔG and Achieve Sustained Virologic Response With Direct-Acting Antiviral Therapy. (26th August 2019) - Emmanuel, Benjamin; El-Kamary, Samer S; Magder, Laurence S; Stafford, Kristen A; Charurat, Man E; Chairez, Cheryl; McLaughlin, Mary; Hadigan, Colleen; Prokunina-Olsson, Ludmila; O'Brien, Thomas R; Masur, Henry; Kottilil, Shyam
Abstract: Background: Clearance of hepatitis C virus (HCV) results in rapid changes in metabolic parameters early in direct-acting antiviral (DAA) therapy. Long-term changes after sustained virologic response (SVR) remain unknown. Methods: We investigated longitudinal changes in metabolic and inflammatory outcomes in chronic hepatitis C (CHC) patients: low-density lipoprotein (LDL), high-density lipoprotein, triglycerides, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) using a general linear model for repeated measurements at 5 clinical time points and by human immunodeficiency virus (HIV) coinfection and IFNL4 genotype. Results: The mean LDL increased markedly during DAA therapy (pre-DAA, 86.6 to DAA, 107.4 mg/dL; P < .0001), but then it decreased to 97.7 mg/dL by post-SVR year 1 ( P < .001 compared with DAA; P = .0013 compared with SVR). In patients who carry the IFNL4 -ΔG allele, mean LDL increased during treatment, then decreased at post-SVR year 1; however, in patients with TT/TT, genotype did not change during and after DAA treatment. The mean ALT and AST normalized rapidly between pre-DAA and DAA, whereas only mean ALT continued to decrease until post-SVR. Metabolic and inflammatory outcomes were similar by HIV-coinfection status. Conclusions: Changes in LDL among CHC patients who achieved SVR differed by IFNL4 genotype, which implicates the interferon-λ4 protein in metabolic changes observed in HCV-infected patients.